Impactos da imigração no mercado de trabalho brasileiro - Machado, Flávio A. de Stéfani (2015)
Given the importance that the immigration issue has acquired in the country in recent years, it generated a need for better understanding of the economic effects caused by population inflows of this nature. Nonetheless, to the authors’ knowledge, there are no studies for the recent Brazilian history regarding the impacts of immigrants on the labor market outcomes, in particular, on natives’ wage and employment level. With this background in mind, the studies carried out in this thesis aim to give the first steps in the research of this subject. The present work is composed of four chapters, which examine different issues associated to the effects of immigration on Brazilian labor market.The first chapter motivates the immigration issue in Brazil and, by means of a structural methodology based on the CES production function framework, simulates the effect on the wage structure in response to immigration influxes stipulated for the year 2010, date of the last Demographic Census. In particular, we calculate a mean wage impact around −0.25% resulting from a stipulated influx of 549 thousands immigrants, same magnitude of the one observed between December 2010 and December 2011. The second chapter estimates the degree of substitution between immigrants and natives of the same skill group and tests the assumption of perfect substitution empirically supported by Borjas et al. (2012, 2008) and adopted in the previous chapter. The employed methodology is based upon the structural framework developed in Manacorda et al. (2012) and Ottaviano & Peri (2012), which adds an extra level to the nested CES production function of Borjas (2003). The estimated elasticities of substitution under several model specifications varies from 9 to 23, results that strengthen the imperfect substitution thesis preconized by Card (2012). The third chapter estimates two types of elasticities related to the impacts of immigrants on natives’ wage through an alternative methodology based on a more flexible production function that is not subject to constraints as stringent as multi-level CES is. The computed estimates for the underlying Hicks elasticities of substitution lie between 1.3 and 4.9, which reinforces the evidences of imperfect substitution obtained in Chapter 2. Moreover, the estimated gross elasticities of natives’ wages with respect to the quantities of immigrants in production are at most of the order of +−0.01. The fourth and last chapter, by means of a methodology founded on the Translog cost function framework, examines how the native’s employment level responds to changes in the cost of immigrant labor, issue that so far has been given little attention in the literature, despite its relevance to the formulation of immigration policies. To all model specifications and education groups considered, our results indicate that an exogenous variation in immigrant’s wage leads to only slightly effects on the level of employment of Brazilian native workers. In most cases, the hypothesis that native and immigrant are neither net p-complements nor net p-substitutes cannot be rejected